2015
DOI: 10.1007/s00572-015-0643-6
|View full text |Cite
|
Sign up to set email alerts
|

Transcript profiling of aquaporins during basidiocarp development in Laccaria bicolor ectomycorrhizal with Picea glauca

Abstract: Sporocarp formation is part of the reproductive stage in the life cycle of many mycorrhizal macrofungi. Sporocarp formation is accompanied by a transcriptomic switch and profound changes in regulation of the gene families that play crucial roles in the sporocarp initiation and maturation. Since sporocarp growth requires efficient water delivery, in the present study, we investigated changes in transcript abundance of six fungal aquaporin genes that could be cloned from the ectomycorrhizal fungus Laccaria bicol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…We detected the aquaporin gene specifically induced in primordia and stipe tissues ( Fig 2B ; S2A Fig ; S4 Table ). Aquaporins are integral membrane proteins responsible for water and solute transport, and also involved in mycorrhizal formation and plant-fungal interactions during symbiosis establishment [ 26 , 61 ]. Recent study revealed that aquaporins were also developmentally regulated in L .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We detected the aquaporin gene specifically induced in primordia and stipe tissues ( Fig 2B ; S2A Fig ; S4 Table ). Aquaporins are integral membrane proteins responsible for water and solute transport, and also involved in mycorrhizal formation and plant-fungal interactions during symbiosis establishment [ 26 , 61 ]. Recent study revealed that aquaporins were also developmentally regulated in L .…”
Section: Resultsmentioning
confidence: 99%
“…Aquaporins are integral membrane proteins responsible for water and solute transport, and also involved in mycorrhizal formation and plant-fungal interactions during symbiosis establishment [26,61]. Recent study revealed that aquaporins were also developmentally regulated in L. bicolor fruiting bodies [26]. However, aquaporins have been discussed mostly in the context of mycorrhizal fungi [62][63][64][65].…”
Section: Notable Genes During Fruiting Body Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Differential expressions of fungal aquaporins were also observed in a cellspecific pattern, in EcM root tips, free-living mycelium, fungal mantle, Hartig net, and fruiting body. The accumulation of transcripts of Tuber melanosporum aquaporins in the mantle of mycorrhizal tips (Hacquard et al, 2013), the upregulation of several aquaporins in the formation of the fruiting body of L. bicolor (Xu et al, 2016), and the striking upregulation of two aquaporin genes of EcM Cenococcum geophilum induced by the symbiosis interaction with Pinus silvestris (Peter et al, 2016), are some examples of the physiological significance of fungal aquaporins in hyphal cells and at hypharoot interface.…”
Section: Roles Of Fungal Aquaporins In Ectomycorrhizal Root Water Tramentioning
confidence: 99%
“…Agroclimatic parameters, such as precipitation or temperature, determine the annual crop for other Basidiomycota mycorrhizal fungi before or during the fruiting season (Martínez-Peña et al 2012). However, unlike the fruiting bodies of other Basidiomycota mycorrhizal fungi, which develop in few days (Teramoto et al 2012;Xu et al 2016), in the case of Ascomycota such as Tuber and Terfezia, their development is slower and usually takes several months (Olivier et al 2012;Le Tacon et al 2014). Therefore, it is expected that long-term environmental factors may influence their development, as has been observed in black truffle (Baragatti et al 2019).…”
Section: Introductionmentioning
confidence: 99%